Current Status of Advance Care Planning and End‐of‐life Communication for Patients with Advanced and Metastatic Breast Cancer. (2nd January 2021) - Sagara, Yasuaki; Mori, Masanori; Yamamoto, Sena; Eguchi, Keiko; Iwatani, Tsuguo; Naito, Yoichi; Kogawa, Takahiro; Tanaka, Kiyo; Kotani, Haruru; Yasojima, Hiroyuki; Ozaki, Yukinori; Noguchi, Emi; et al.
Abstract: Background: Advance care planning (ACP) is a process that supports adults in understanding and sharing their personal values, life goals, and preferences regarding future medical care. We examined the current status of ACP and end‐of‐life (EOL) communication between oncologists and patients with metastatic breast cancer. Materials and Methods: We conducted a survey among 41 institutions that specialize in oncology by using an online tool in October 2019. Participants (118 physicians) from 38 institutions completed a 39‐item questionnaire that measured facility type and function; physicians' background and clinical approach, education about EOL communication, and understanding about ACP; and the current situation of ACP and EOL discussions. Results: Ninety‐eight responses concerning physicians' engagement in ACP with patients were obtained. Seventy‐one (72%) answered that they had engaged in ACP. Among these, 23 (33%) physicians used a structured format to facilitate the conversation in their institutions, and only 6 (8%) settled triggers or sentinel events for the initiation of ACP. In the multivariable analysis, only the opportunity to learn communication skills was associated with physicians' engagement with ACP (odds ratio: 2.8, 95% confidence interval: 1.1–7.0). The frequency and timing of communication about ACP and EOL care with patients substantially varied among the oncologists. Communication about patients' life expectancy was less frequent compared with other topics. Conclusion: The opportunity to improve EOL communication skills promoted physicians' engagement with ACP among patients with metastatic/advanced breast cancer. However, there were still substantial variabilities in the method, frequency, and timing of ACP and EOL communication among the oncologists. Implications for Practice: This study found that the opportunity to improve end‐of‐life (EOL) communication skills promoted physicians' engagement in advance care planning (ACP) among patients with metastatic/advanced breast cancer. All oncologists who treat said patients are encouraged to participate in effective education programs concerning EOL communication skills. In clinical practice, there are substantial variabilities in the method, frequency, and timing of ACP and EOL communication among oncologists. As recommended in several clinical guidelines, the authors suggest a system that identifies patients who require conversations about their care goals, a structured format to facilitate the conversations, and continuous measurement for improving EOL care and treatment. Abstract : The purpose of advance care planning is to enable individuals to make plans about their future health care and improve discussions about end‐of‐life care and treatment. This article examines the current status of advance care planning for patients with advanced metastatic breast cancer to determine factors associated with physician engagement in institutions that specialize in oncology.